Mesenchymal stem cells target microglia via galectin-1 production to rescue aged mice from olfactory dysfunction - Seo, Yoojin; Ahn, Ji-Su; Shin, Ye Young; Oh, Su-Jeong; Song, Min-Hye; Kang, Min-Jung; Oh, Jung-Min; Lee, Dongjun; Kim, Yun Hak; Lee, Byung-Chul; Shin, Tae-Hoon; Kim, Hyung-Sik (Biomedicine & pharmacotherapy, 2022)
Olfactory loss has been considered as the earliest complication for the aging process while underlying mechanisms and therapeutic strategies remain unclear. Given the correlation between microglial activation and olfactory dysfunction, here we investigated whether the immunomodulatory action of mesenchymal stem cells (MSCs) can rescue the olfactory impairment in old mice. The intranasal delivery of MSCs limited microglial activation and neuronal apoptosis in the olfactory bulb (OB), leading to improvement in olfaction. MSCs down-regulated the proportion of CD86+ microglia and prevented the maturation of cathepsin S, one of the inflammatory mediators in olfactory impairment, via the suppression of p38 MAPK signaling. Notably, old astrocytes could not prevent excessive microgliosis because the endogenous production of Galectin-1 (Gal1), one of the key microglia regulators secreted by astrocytes, was not sufficiently upregulated in the aged brain despite the presence of reactive astrogliosis. Considering that Gal1 is known as a potent paracrine factor of MSCs, we investigated whether MSC-derived Gal1 could compensate for defective astrocyte function in terms of microglial regulation. MSCs and their culture supernatant (MSC-CM) could regulate the direction of microglial differentiation by impeding the polarization towards the pro-inflammatory M1 type; notably, a selective Gal1 inhibitor OTX008 could hinder this phenomenon, indicating that Gal1 is involved in immunomodulation exerted by MSCs. Also, acute microglial activation within the OB upon LPS infusion was attenuated by MSC-CM in a Gal1-dependent manner. Our study demonstrates the therapeutic benefit of MSCs on age-related olfactory dysfunction and suggests Gal1 as a key mediator of the anti-inflammatory action of MSCs. [Display omitted] •Excessive microgliosis impairs the olfactory function in the aging context.•The olfactory performance of old mice is significantly improved upon MSC delivery.•MSCs and their secretomes regulate the M1–M2 polarization of microglia.•Galectin-1-dependent microglial regulation of astrocytes is defective in old mice.•Galectin-1 is a key paracrine factor involved in MSC-mediated microglial inhibition.